Dante Gabriel Rossetti e Walter Pater: per un’estetica vittoriana - Moriconi, Chiara (Status Quaestionis, 2012)
The art of the Victorian poet-painter Dante Gabriel Rossetti developed along the boundaries between distinct cultures and artistic systems. His work is marked by a perpetual dialogue between different semiotics, which should be taken into account in order to fully appreciate the dual aesthetics of his works of art. Crucial to illuminate Rossetti’s double work are also the works of Walter Pater, especially his introduction to the “School of Giorgione”.